SISTEM PENGAJUAN DAN PELAPORAN PENGELOLAAN KARYA LIMBAH DI DINAS PERUMAHAN DAN PERMUKIMAN - Moh. FirmanSyah p.; Abd. Wahab Syahroni; Nilam Ramadhani; Nindian Puspa Dewi (Insand Comtech : Information Science and Computer Technology Journal, 2022)
AbstractSubmission and reporting is an amalgamation originating from regional accounting entities that receive deconcentration funds, auxiliary duty funds and joint task funds. Submission and reporting is the result of the accounting process that can be used as a tool for communication of financial data or regional institutions to the parties concerned. It could be said that this submission and reporting serves as information that connects regional institutions with the parties concerned. The submission and reporting provides information about economic resources and reporting obligations to report the results of the submission on a specified date as well as the flow of economic resources during the period. walk. This information is needed by interested parties to assess the reporting entity's ability to carry out future activities. the party responsible for providing information to assist users in estimating the results of operations and management.Keywords: Filing Analysis and Financial Statements Keywords: analysis of submussions and financial statements